2020
DOI: 10.1177/2158244020963590
|View full text |Cite
|
Sign up to set email alerts
|

Dependency as Status: Older Adults’ Presentations of Self as Recipients of Care

Abstract: We draw on Bourdieu’s and Goffman’s theories to elaborate the novel idea of dependency as status in old age, a concept that emerged from our Grounded Theory study conducted with 46 older adults (26 women and 20 men) living in and around Dublin, Ireland. The research participants’ portrayals of (in)dependence and assistance reflected their access to and use of social and symbolic (age) capital. Older adults derived social capital from supportive family relations or trusting relationships with formal care provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…14 Old age and the need for help should be valued by society. 22 Our findings also showed that several of the older persons had moved from their previous homes into flats, and several of them stated that they continued to consider their previous housing arrangement as their home. The move to a new residence may be necessary due to health problems.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…14 Old age and the need for help should be valued by society. 22 Our findings also showed that several of the older persons had moved from their previous homes into flats, and several of them stated that they continued to consider their previous housing arrangement as their home. The move to a new residence may be necessary due to health problems.…”
Section: Discussionsupporting
confidence: 60%
“…14 Healthcare professionals, such as home care nurses, should offer their services in a way that confirm the worth and eligibility for assistance of an older person. 19,22 In our study, some older persons expressed that receiving the help they needed was challenging, and communicated a type of resignation regarding organizational structures in the healthcare system. In another study, older persons expressed that the availability of information regarding help and access to resources affected their sense of belonging.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this study, individuals who require assistance from others to perform their daily tasks are considered dependent. From a medical perspective, we understand the dependency of older adults as a state of chronic or temporary functional disability that leads to the inability to do tasks that could be previously performed alone [45,46]. One significant independent risk factor for depression in this study was dependency.…”
Section: Discussionmentioning
confidence: 85%
“…Old age is one such time in life, as general wear and tear, greater susceptibility to disease, and decreased regenerative capability lead to an accumulation of deficits, increasing the likelihood of dependence. In medical contexts, dependency is considered an outcome of temporary or chronic functional disability, which necessitates reliance on others to perform tasks that could previously be performed alone (Timonen and Lolich 2020). There is considerable overlap between concepts of dependence, disability, and frailty; however, in recent years researchers have favored the conceptualization of frailty to describe the state in which independence is most compromised.…”
Section: Introductionmentioning
confidence: 99%